Opinions and behavior of family doctors concerning vaccinating against influenza - Gutknecht, Piotr; Winiarski, Tomasz; Trzeciak, Bartosz; Molisz, Andrzej; Pietrzykowska, Małgorzata; Nowicka-Sauer, Katarzyna; Siebert, Janusz (Family Medicine & Primary Care Review, 2016)
Background. Influenza is a severe respiratory disease caused by influenza virus. According to estimates from the World Health Organisation (WHO), 5–15% of the world’s population, or 330–1575 million people, suffer from influenza each year. The vaccination of patients and health professionals plays an important role in the prevention of infections. Objectives. To describe family doctors’ opinions and behavior concerning influenza vaccination. Material and methods. An online survey was filled out by 77 family physicians, of whom women accounted for 53.5%. The age mean of the doctors surveyed was 44.6 ± 11.7 years. The questionnaire contained 14 questions. Results. 63.6% (49 people) of the respondents were worried about flu, and 84.4% (65 people) were concerned about the possibility of their family members being infected. 77.9% (60 people) approve of vaccination. 51.5% (40 people) of the doctors received the vaccination in the current (2015/2016) influenza season. 18.2% (14) of the respondents were vaccinated within the last five seasons. The respondents recommended vaccination against influenza to their families sometimes (50.6%, 39) or frequently (41.6%, 32). They recommended the vaccination to their patients frequently (41.6%, 32) or sometimes (53.2%, 41). Only 18.2% (14) of the respondents were covered by the free vaccination program in their workplace. As many as 76.6% (59) of the doctors would recommend the vaccination more often if it were free, and 44.2% (32) would be more willing to recommend the vaccination if they received additional payment for it. When doctors were asked why they thought patients did not have themselves vaccinated, the reasons most frequently given were: patients’ lack of time and awareness of the disease consequences and complications (57.1%, 44), patients’ fear of postvaccination reactions (44.2%, 34), inconvenience associated with vaccination, including the cost of the vaccine (42.9%, 33), patients’ belief that vaccination is ineffectiveness, that the risk of infection is low, or that they do not belong to a risk infection group (28.6%, 22) and, finally, inconvenient vaccination hours (7.8%, 6). Conclusions . 1. Family doctors are fully aware of the importance of vaccinating against influenza. However, this awareness is not reflected in the immunization rates among medical personnel. 2. More than half of the practitioners recommend vaccination to their patients. 3. The fear of supposed complications and financial problems are the most often indicated reasons for not being vaccinated against influenza.